2001
DOI: 10.1023/a:1005689230013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of jury instructions on the fusion of liability and compensatory damages.

Abstract: This study examined whether special jury instructions or the bifurcation of liability and compensation decisions would counter the tendency for evidence concerning the defendant's liability to affect damages awards. Mock jurors made liability and award decisions in response to a case description in which the level of defendant responsibility for the plaintiff's injuries and the type or timing of damages instructions were systematically varied. Instructions not to discount awards for uncertainty about the defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
0
32
1
Order By: Relevance
“…This finding is inconsistent with a legal approach that assumes that jurors reliably separate liability and damages decisions (Wissler, Rector, & Saks, 2001). Liability was not entirely fused with pain and suffering—regressions showed that each contributed unique variance to damage awards.…”
Section: Discussionmentioning
confidence: 79%
“…This finding is inconsistent with a legal approach that assumes that jurors reliably separate liability and damages decisions (Wissler, Rector, & Saks, 2001). Liability was not entirely fused with pain and suffering—regressions showed that each contributed unique variance to damage awards.…”
Section: Discussionmentioning
confidence: 79%
“…This is similar to how jurors have allocated damages in past research (Wissler et al, 2001) and in some jurisdictions; however, most jurisdictions do not separate out these damage claim amounts. Thus, legal scholars who analyze damages to examine differences in the components of these damage award amounts are forced to use other means (e.g., insurance claims) to try and determine how much of a final award should be allocated to each component of the claim (Vidmar, 1994).…”
Section: Limitationsmentioning
confidence: 81%
“…They provided dollar amounts in each of several categories for both compensatory (i.e., lost wages, future lost wages, medical expenses, future medical expenses, and pain and suffering) and punitive (i.e., to punish the defendant for inappropriate behavior, to deter the defendant from similar behavior in the future, and to deter other companies from similar behavior) damages, similar to the damage award allocations made by participants in past research (e.g., Wissler, Rector, & Saks, 2001) and similar to some jurisdictions (e.g., Maryland, New York) that use special verdicts that allow juries to allocate the amount of damages for each component of the claim (Vidmar, 1994).…”
Section: Dependent Measuresmentioning
confidence: 90%
“…Jurors often have difficulty separating the liability assessment from the damage assessment, even when given specific instructions to consider damages based solely on the plaintiff"s injury. This "fusion" of the liability and damage assessments is commonly attributed to jurors discounting the award because of uncertainty about the defendant"s liability (Wissler et al 2001). Research has found that jurors who were doubtful about the defendant"s liability compromised with other jurors on liability in exchange for a reduced award (Hans and Lofquist 1992), and compensatory awards were lower when the defendant"s fault was ambiguous than when the defendant"s fault was clear (MacCoun 1996).…”
Section: H1mentioning
confidence: 99%